Estimulação elétrica com eletrodos não implantáveis no tratamento da bexiga hiperativa em adultos: revisão sistemática de ensaios clínicos randonizados - Gameiro, Luís Felipe Orsi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: Overactive bladder (OAB) is a clinical syndrome characterized by urgency with or without incontinence is usually concurrent by urinary frequency in the absence of urinary tract infection or other bladder disorders. However there is no consensus in the literature that who is the most better method of treatment for overactive bladder.You can reach millions of individuals of both sexes throughout the world and cause major impact on quality of life. The treatment using electrical stimulation (ES) has been recommended as first-line therapy. Objective: To acess the efficacy and safety of electrical stimulation with non-implantable electrodes for the treatment of overactive bladder when compared to other types of treatment or placebo. Type of study: Systematic review of randomized clinical trials.Search Strategy: Medline, CENTRAL, EMBASE and Lilacs databases were searched. The last search was on January 12, 2014 Criteria for the selection of studies: clinical trials that evaluated the treatment of electrical stimulation compared with nonimplanted electrodes or with other types of treatment were included. Data collection and analysis: Two reviewers independently selected relevant studies, assessed the quality methodological and extracted data.Results: 30 studies were included, with a total of 1.785 participants. The methodological quality of the studies was unclear risk of bias all the most domains. Six studies generated five graphs of meta-analysis. The first meta-analysis with two studies (Barroso 2004; Yamanishi 2000) compared electrical stimulation versus sham on the outcome maximum bladder capacity there was a statistically significance difference favouring electrical stimulation (MD 105.52 [95%CI 63.62 to 147.42], p<0.00001, I²=0%).The second meta-analysis with two studies (Arruda 2008; Schreiner 2010) compared the electrical stimulation (ES) versus pelvic floor muscle trainning (PFMT) on the outcome of urinary ...

Introdução: Bexiga hiperativa (BH) é uma síndrome clínica caracterizada por urgência urinária, com ou sem incontinência é geralmente acompanhada por aumento da frequência miccional na ausência de infecção urinária ou de outras patologias na bexiga. Entretanto, até o momento não existe consenso na literatura de qual o melhor método de tratamento para BH. Pode atingir milhões de indivíduos de ambos os sexos em todo o mundo e causar grande impacto na qualidade de vida. O tratamento utilizando estimulação elétrica (EE) têm sido recomendado como terapia de primeira linha. Objetivo: Determinar a eficácia e segurança da estimulação elétrica (EE) com eletrodos não implantáveis no tratamento da bexiga hiperativa quando comparada a outras formas de tratamento ou placebo. Tipo de estudo: revisão sistemática de ensaios clínicos randomizados. Estratégia de busca: Foram pesquisadas as bases de dados Medline, CENTRAL, Embase e Lilacs. A última busca foi em 12 de janeiro de 2014. Critério para a seleção dos estudos: Foram incluídos ensaios clínicos que avaliaram o tratamento de EE com eletrodos não implantáveis comparados ou associados a outros tipos de tratamento. Análise e coleta de dados: Dois revisores selecionaram independentemente os estudos relevantes, avaliaram a qualidade metodológica e extraíram os dados. Resultados: Foram incluídos 30 estudos, com um total de 1.785 participantes. A qualidade metodológica dos estudos foi incerta para risco de viés na maior parte dos domínios. Seis estudos geraram cinco gráficos de metanálise. A primeira metanálise com dois estudos (Barroso 2004; Yamanishi 2000) comparou a estimulação elétrica versus sham na capacidade cistométrica máxima, houve diferença estatisticamente significativa a favor da estimulação elétrica (MD 105.52 [95%CI 63.62 to 147.42], p<0.00001, I²=0%). A segunda metánalise com dois estudos (Arruda 2008; Schreiner 2010) comparou a ...
Keywords: Bexiga - Doenças; Estimulação elétrica; Ensaios clínicos; Eletrodos; Revisão; electrical stunning; Bladder